Preterm Birth, Kidney Function and Cardiovascular Disease in Children and Adolescents - Athanasia Chainoglou; Katerina Chrysaidou; Vasilios Kotsis; Stella Stabouli (Children, 2022)
Over recent decades, there has been a global increase in preterm birth rate, which constitutes about 11% of total births worldwide. The present review aims to summarize the current knowledge on the long-term consequences of prematurity on renal and cardiovascular development and function. Recent literature supports that prematurity, intrauterine growth restriction or low birth weight (LBW) may have an adverse impact on the development of multiple organ systems, predisposing to chronic diseases in childhood and adulthood, such as arterial hypertension and chronic kidney disease. According to human autopsy and epidemiological studies, children born preterm have a lower nephron number, decreased kidney size and, in some cases, affected renal function. The origin of hypertension in children and adults born preterm seems to be multifactorial as a result of alterations in renal, cardiac and vascular development and function. The majority of the studies report increased systolic and diastolic blood pressure (BP) in individuals born preterm compared to full term. The early prevention and detection of chronic non-communicable diseases, which start from childhood and track until adulthood in children with a history of prematurity or LBW, are important.